The Role of Family Medicinal Plant Education (TOGA) in the Development of Living Pharmacies to Support the Availability of Emergency Medicines in Pilubang Village - Yanti Nopita; Nur Halizha; Nadia Permata Putri Munthe; Ade Yusuf; Ferdi Rahman; Muhammad Husein Al-Kautsar (Sean Institute, 2026)
The availability of emergency medicines in remote areas with limited healthcare access is a crucial issue. The development of Family Medicinal Plants (TOGA) through the concept of a living pharmacy presents a strategy to achieve community independence in providing traditional medicines. This community service activity aims to increase the knowledge, skills, and awareness of the Pilubang Village community in planting, caring for, and utilizing medicinal plants. Implementation methods include interactive counseling on plant types and benefits, practical demonstrations of planting techniques, and assistance in making products such as instant ginger drinks and aloe vera ointments. Evaluation results show a significant increase in participant understanding, the formation of a village living pharmacy management group, and the availability of a variety of ready-to-use medicinal plants for family first aid. This program has proven effective in strengthening community health independence and can serve as a model for sustainable TOGA management at the village level.